France, Europe and the United States: New Realities of an Old Alliance - Poncet, Jean-Francois (Tufts Archival Research Center, 2005)
Volume 5, Issue 2. Summer On February 26, 1981 His Excellency Jean Francois-Poncet delivered the annual William L. Clayton lecture at the Fletcher School. In his address, the former French Minister of Foreign Affairs discusses the current status of the United States' oldest ally and its foreign relations today. He contends that if the Western alliance is to sustain itself both Americans and Europeans must overcome their tendencies toward mutual criticism of each other's policies and learn to speak to each other frankly, confidently and in good faith. His Excellency Franois-Poncet graduated from The Fletcher School in 1948.